Personal Learning Environments (PLE) Among Malaysian Students - Tee, Tze Kiong; Nur Rahma Putra, Andika Bagus; Sutadji, Eddy; Hamzah, Norkhairolizah; Abbas@Ahmad, Lutfiah Natrah; Yusof, Yusmarwati (Online Journal for TVET Practitioners, 2025)
The paper aims to explore the correlations between Malaysian students Personal Learning Environments PLE in terms of four significant factors; self-concept, planning and management, tool & resource utilization as well as social interaction. The emphasis is on variances such as in age, gender and wealth. Out of 198 students aged 13 to 17, the data indicated that 66.2% scored "High" in social interaction, with similar numbers for use of tools and resources (72.7%), planning and management (80.8%), and self-concept (84.8%). These qualities are only very slightly correlated with age, as older student generally perform better. To take one example, 92% of that solenoid needed for 17-year-olds were scored as "High" in Self-Concept than just 70% of those solenoid needed for 13-year-olds. Gender Differences: In all dimensions, women outperform men and employ Planning Tools and group learning effectively with PLE tools. Limitations such as limited access to technology compound wealth disparities, meaning many lower-income students experience very different patterns of social interaction and resource utilization. Our findings highlight the need for inclusive PLE designs and targeted interventions, such as equitable access to digital devices and tools; gender-sensitive design features, and personalised supports—if PLE benefits are to be maximised for diverse learner populations.